MOLECULAR GENETIC PLANT ANALYSIS, ARTEMISIA L. GENUS, WITH ISSR-MARKERS - Rakhymberdieva Zhanar Sherahmetovna; Kaliyeva Anar Nurgaiypovna; Medeuova Galiya Dzhumahanovna (Academic Journal of Physical and Chemical Sciences, 2020)
Molecular genetic analysis of three plants of thistle family has been carried out in the scope of this paper (Artemisia karatavica Krasch. & Abolin ex Poljakov, Artemisia cina Berg ex Poljakov, Artemisia porrecta Krasch. ex Poljakov). The plants have been collected in Turkestan region, Shardarinsky district, 15 km north-east of the village Komsomol, and along the road in Turkestan region, Baydibeksky district, 4.5 km south-east of the village Shakpak, and in the steppes in Turkestan region, Aryssky district, 1 km north-east of the village Darmino. In this paper, we used modern methods of molecular biology in order to determine genetic relatedness. ISSR analysis using universal primers has been conducted. ISSR-markers are the most common markers, and they are used for phylogenic analysis. This method is based on amplification of sequences limited by two microsatellite repeats using the primer that is complementary to the sequence of this microsatellite (4-12 repeat units). ISSR (region of the genome between two adjacent, oppositely oriented microsatellites) the sequence of microsatellite medullar part with some (1-3) nucleotides adjacent to the repeat tandem are used as primers. Tens of fragments of locus variety received in PCR are separated by electrophoresis and assessed for the presence or absence (due to marker dominance) of the fragments of a particular size. The main advantage of this type of markers - lack of necessity for knowledge of the sequences during primer designing.